Biofiltration of methane and trace gases from landfills: a review - Menard, C.; Ramírez, A.A.; Nikiema, J.; Heitz, M. (Canadian Science Publishing, 2012)
Concerns about biogas from landfills are reviewed in terms of biogas generation, composition, and elimination. Biogas is mainly composed of methane and carbon dioxide but it also contains a few hundred non-methane organic compounds. The solutions available to reduce its harmful effects on the environment and on human health are valorization as electricity or heat, flaring, or biofiltration. The main parameters affecting the biofiltration of methane are reviewed: temperature, moisture content, properties of the packing material, nutrient supply, oxygen requirements, formation of exopolysaccharides, and gas residence time. An analysis is performed on the co-metabolic properties and the inhibition interactions of the methane-degrading bacteria, methanotrophs.